Conserving Energy through Energy Management by the Facility Managers in India (Global Journals of Research in Engineering, 2019)
Facility Management in IT sector is a booming businessin India today IT companies expect the facility should be always ready for use to meet their business operational requirements without any hindrance Property owner need an external agency to ensure that demand is met at all the times That is why Facility Management Company is in demand but Energy Conservation is a lost priority as it does not fit into anyone s requirement If Energy Conservation for operational excellence is made part of the property rental agreement then it will fit into everyone s requirement Studies have shown the Facility Manager can save energy without any expenditure just by fine tuning the equipment operations as it is one of his major responsibilities Facility Managers experienced in Energy Management strongly believe that if Energy Conservation is incorporated into the Facility Management activities as part of the contractual obligation then it is very much possible to reduce the total energy requirement to run the facility without compromising with the comfort level output This saving in energy cost will directly benefit to all parties concerned
Keywords: energy management; facility management; energy conservation